Weakly-coupled real-time SDM technology for short-reach optical transmission - Yuyang GAO; Juhao LI; Yongqi HE; Zhangyuan CHEN (Dianxin kexue)
The capacity upgrade of short-reach optical fiber transmission has received more and more attention.Spatial division multiplexing provides two new dimensions of fiber core and mode, which can greatly increase the transmission capacity of a single fiber.However, the crosstalk between spatial channels severely limits the practical application of space division multiplexing technology.To address the problem, a weakly-coupled space-division multiplexing fiber was firstly designed, in which perturbed rings were introduced in the core to increase the effective refractive index difference between LP modes.Secondly, an all-fiber mode multiplexer/demultiplexer that could handle non-circularly symmetric degenerate LP modes was proposed, as well as a low insertion loss and low crosstalk fan-in and fan-out devices.Based on the proposed fiber and devices, the low-cost intensity modulation and direct detection were used to implement the short-reach weakly-coupled mode-division-multiplexing and multi-core and few-mode real-time transmission.Finally, the prospective of space-division multiplexing real-time optical transmission technology was discussed.